PERANAN FIRMAN ALLAH DALAM PELAYANAN KONSELING PASTORAL YANG HOLISTIK - Esther Rela Intarti (Regula Fidei: Jurnal Pendidikan Agama Kristen, 2018)
The meaning of a general counseling is a reciprocal relationship carried out by the counselor to provide the opportunity for the counselee to explore their feelings, discover what problems they faces and explore the counselee's own potential and find the ways to overcome problems bocome a more comfortable and satisfying life. The role of the God’s word in a holistic pastoral counseling service places the God’s word to become the foundation and provide direction and achievement of counseling by looking thoroughly at all aspects of the counselee. It can also be said that the word of God can be an absolute standard of truth. The God’s word in the pastoral counseling process can give enlightenment to the meaning of life and wisdom to the problems faced to obtain a solution. The role of the God’s word does not just stop as the giver of light, but the God’s word is also able to provide a measure of the highest values or norms. The role of the God’s word is a central in resolving or living the life problems of the counselee as a believer because the God’s word is a source that gives us power, strength, willingness and wisdom in helping, entertaining, and strengthening those who are helpless. For counselees, the God’s word can be awaken them from their sins and mistakes which ultimately change their hearts and characters towards a better life change. Abstrak: Konseling secara umum merupakan hubungan timbal balik yang dilakukan oleh konselor untuk memberikan kesempatan konseli mengekplorasi perasaan-perasaannya, menemukan apa masalah yang dihadapinya serta menggali potensi diri konseli dan menemukan cara untuk mengatasi persoalan agar hidup yang lebih nyaman, dan memuaskan. Peranan firman Allah dalam pelayanan konseling pastoral yang holistik adalah menempatkan firman Allah untuk dijadikan landasan dan memberikan Arah serta pencapaian konseling dengan melihat secara menyeluruh seluruh aspek dalam diri konseli. Hal ini dapat juga dikatakan bahwa firman Allah dapat menjadi standar kebenaran yang mutlak. Firman Allah dalam proses pastoral konseling dapat memberi pencerahan makna kehidupan dan hikmat terhadap persoalan yang dihadapi untuk memperoleh jalan penyelesaiannya. Peranan firman Allah tidak hanya berhenti sebagai pemberi terang, tetapi firman Allah juga mampu memberikan ukuran dari nilai-nilai atau norma yang paling tinggi. Peran firman Allah sangat sentral dalam menyelesaikan atau menjalani masalah kehidupan konseli sebagai orang percaya karena firman Allah merupakan sumber yang memberikan kita kuasa, kekuatan, kemauan, dan kebijaksanaan dalam menolong, menghibur, dan menguatkan mereka yang sedang tidak berdaya. Bagi konseli, firman Allah mampu menyadarkan mereka dari dosa dan kesalahannya yang pada akhirnya mengubah hati dan karakter mereka menuju perubahan hidup yang lebih baik.